Nutritive values of Cajanus cajan by products as ruminant feed - Abidinsyah, Dian Agustina; Yaakub, H.; Suyub, Iswan Budy; Jusoh, S. (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Cajanus cajan (L.) Millsp is Fabaceae family (alt. Leguminosae). It has different common name the most common is congo pea, pigeon pea or yellow dahl. The morphological of the plant is an annual or short-lived perennial shrub or small tree with leaves trifoliate, alternate, set in a spiral around the stem, flowers usually yellow and a flat pods (5–9 cm long, 12–13 mm wide, containing 2–9 oval to round seeds varying in colour from light beige to dark brown) that can grow up to one to four meters and usually with an erect woody at the base. Cajanus cajan primarily grown as a grain crop for seed for human consumption with over 4 million hectares cultivated worldwide. The foliage may be cut and fed to livestock fresh or conserved. This study was conducted to evaluate the nutritive values of Cajanus cajan by products (leave and pods husk) in comparison with concentrate. Commercial concentrate (C) and Cajanus cajan leave (CCL) and pod husk (CPH) samples (after harvesting at 8 months of age) were collected from South Sulawesi, Indonesia. Proximate analysis, acid detergent fibre, neutral detergent fibre and acid detergent lignin were conducted. The results indicate that the ash (7.6%DM; 7.3%DM), NDF (47.7%DM; 46.4%DM) and ADL (15.3%DM; 16.8%DM) for CCL and C were not different (P>0.05), respectively. The crude protein (20.9%DM; 16.1%DM) and ADF (28.2%DM; 21.9%DM) were significantly higher (P<0.05) in CCL compared with C. The nutritive values for CPH for ash, crude protein were significantly lower (P<0.05) and NDF (77.6%DM), ADF (67.0%DM) and ADL (32.3%DM) were significantly higher (P<0.05) compared with both CCL and C. In conclusion, based on the nutritive values of Cajanus cajan leave it has a potential as ruminant feed.